If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 + 8x + -55 = 180 Reorder the terms: -7 + -55 + 5x + 8x = 180 Combine like terms: -7 + -55 = -62 -62 + 5x + 8x = 180 Combine like terms: 5x + 8x = 13x -62 + 13x = 180 Solving -62 + 13x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '62' to each side of the equation. -62 + 62 + 13x = 180 + 62 Combine like terms: -62 + 62 = 0 0 + 13x = 180 + 62 13x = 180 + 62 Combine like terms: 180 + 62 = 242 13x = 242 Divide each side by '13'. x = 18.61538462 Simplifying x = 18.61538462
| 4x+7=47+2x | | 1/4x-7=1 | | 7(x-4)+2=51 | | f(t)=-16t^2+104t+56 | | 9s+7s= | | (6+4i)(3-7i)=0 | | -2(6y-5)= | | 6x+2xy=3+y | | 13m+4=12 | | 13-a=9 | | 4x+23+10x-1=180 | | 3x+12y+15z= | | 2ln(4)=x | | -6y=14 | | 4*2x+1=1024 | | 8-(3n-8)=9-4n | | f(x)=0.05x+30 | | b=a-14 | | -6-2x+4y=0 | | s+3.5=6 | | 3x^3+21x^2+50x+52=0 | | x/2-7x-44=0 | | 9x-73+3x+23=180 | | (x+3)(x-5)=5x-9 | | 5x/2}-x=x/6-8/3 | | 3x-2+7x+3= | | ln(x+1)+ln(x-3)=ln(3) | | g(x)=x^2-18x-8 | | 15x+7+23x-17=180 | | K-1/0 | | ln(x^4)-2ln(x)=1 | | 4x^2+36x-180=0 |